Coulié, Anne 2013. La céramique grecque aux époques géometrique et orientalisante (XIe–VIe siècles av.J.-C.). - Dickinson, Oliver (Journal of Greek Archaeology, 2018)
This is a finely produced volume, but the title of the series to which it belongs is significant. It is a manual, written in clear, uncomplicated French, which provides information in a succinct way, but includes more detail than most people will need about these interesting phases of Greek pottery, even (from the reviewer’s experience) if they are teaching them as part of a university course in Greek art. But it will be generally useful as an up-to-date source of information and comment and should be of considerable value to PhD students specialising in the field.